Match intensity and pacing strategies in rugby league: An examination of whole-game and interchanged players, and winning and losing teams - Black, G. M.; Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2014)
There is currently limited information on whether pacing occurs during rugby league match play. In addition, to date no research has investigated whether pacing strategies differ between winning and losing teams. This study investigated the pacing strategies of whole-game and interchanged rugby league players. Furthermore, we investigated the pacing strategies of winning and losing teams. Fifty-two rugby league players, from a sample of 11 teams competing in a semi-elite competition, underwent global positioning system analysis. Performances were divided into match quartiles for whole-game and interchanged players. Total distance, including low- and high-speed distances, and repeated high-intensity effort bouts were recorded. The total distance and low-speed distance covered across all quartiles of the match, but specifically quartiles 1 and 8, were greater for interchanged players than whole-game players. The match outcome differentially affected the pacing strategies of whole-game and interchanged players. Whole-game players from winning teams set a higher pacing strategy than whole-game players from losing teams (effect size [ES] = 1.03 ± 0.77, 96%, very likely), whereas interchanged players from losing teams demonstrated a greater "end-spurt" than interchanged players from winning teams (ES = 0.60 ± 0.52, 96%, very likely). The pacing strategies of interchanged players were higher than whole-game players, irrespective of playing position. The results of this study suggest that pacing strategies differ between interchanged and whole-game rugby league players. Furthermore, our results demonstrate a different pacing strategy between winning and losing teams. These findings suggest that physical preparation for rugby league matches, and recovery from these matches, should be individualized for whole-game and interchanged players. Finally, performing physically intense training on a regular basis is likely to develop the physical and mental qualities required to regularly compete at higher playing intensities.